2009
DOI: 10.1007/s12237-009-9210-8
|View full text |Cite
|
Sign up to set email alerts
|

A Biogeochemical View of Estuarine Eutrophication: Seasonal and Spatial Trends and Correlations in the Delaware Estuary

Abstract: The Delaware River and Bay Estuary is one of the major urbanized estuaries of the world. The 100-km long tidal river portion of the estuary suffered from major summer hypoxia in the past due to municipal and industrial inputs in the urban region; the estuary has seen remarkable water quality improvements from recent municipal sewage treatment upgrades. However, the estuary still has extremely high nutrient loading, which appears to not have much adverse impact. Since the biogeochemistry of the estuary has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 72 publications
8
83
2
Order By: Relevance
“…20-ml dissolved inorganic carbon (DIC) samples were collected in glass scintillation vials, preserved according to Sharp et al (2009) with 200 lL 5% w/v HgCl 2 and stored in the dark. These data were used for calculating 13 C uptake rates.…”
Section: Detailed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20-ml dissolved inorganic carbon (DIC) samples were collected in glass scintillation vials, preserved according to Sharp et al (2009) with 200 lL 5% w/v HgCl 2 and stored in the dark. These data were used for calculating 13 C uptake rates.…”
Section: Detailed Methodsmentioning
confidence: 99%
“…However, study of estuarine eutrophication globally for more than three decades has revealed a range of ecosystem responses to nutrient enrichment (Sharp, 2001). Increased nutrients may lead to eutrophication with undesirable consequences, but not in all cases (Cloern, 2001;Sharp et al, 2009). Rather than stimulating algal processes, negative effects on phytoplankton physiology have been observed (MacIsaac et al, 1979;Wilkerson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on river discharge conditions, DIC concentrations typically range from about 300 to 1200 µmol kg at the head of the estuary at Trenton (Sharp et al, 2009). During the spring and summer surveys when discharge was high, DIC and TA concentrations were about 300 µmol kg −1 lower than concentrations in the fall when river discharge was low (Fig.…”
Section: Spatial Distributions Of Dic and Tamentioning
confidence: 98%
“…After collection, water was held for 48-h at 50% PAR to allow phytoplankton to reduce the ambient N concentration prior to studying phytoplankton N uptake with increasing NH 4 (Sharp et al, 2009). Samples for inorganic nutrients were passed through a GF/F filter to remove particulate matter before nutrient analysis .…”
Section: Experimental Designmentioning
confidence: 99%